The Arabic Language Learning Curriculum in Modern Islamic Boarding Schools in Gontor Indonesia - Karimah, Fatimatil Imroatil; Putri, Arum Kusmila Surya; Ridho, Ainur (Journal of Arabic Language Studies and Teaching, 2024)
This study explores the curriculum implementation in modern Islamic boarding schools, focusing on Pondok Modern Darussalam Gontor (PMDG). Using a library research approach, data were gathered from books, journals, and online resources. The findings reveal that the Arabic language learning curriculum at PMDG is highly effective due to several supporting factors. Firstly, the immersive language environment extends beyond classrooms into extracurricular activities, applying a guided 24-hour system monitored by the kyai. Secondly, a disciplinary system enforces language usage through specific sanctions for rule violations. Thirdly, the curriculum prioritizes Arabic as the primary medium of instruction. Lastly, the leaders’ consistent use of Arabic serves as a role model for students. This curriculum not only enhances Arabic proficiency but also strengthens students' identity and understanding, contributing positively to Islamic society.